Consistency the Governance and Administration of in- Service Education in the National Education System - Marwan, Marwan (Budapest International Research and Critics University, 2021)
This research has several objectives. First, it examines the consistency and inconsistency of legislations concerning the administration of in-service higher education in the national education system. Accordingly, it analyzes critically the conformity and non-conformity of regulation and administration of higher education with the national education system. Second, it identifies the mechanism of input, process and output of the in-service higher education in the national education system with the laws and regulations concerning the national education system. Third, it finds the concepts and principles of vision in the administration of in-service higher education in the national education system. The research was conducted at in-service universities. Data were collected through literature study (normative law) and field research (empirical law). Data were analyzed qualitatively which is empirical in nature (inductive) by conducting interview, observation and documentation and by combining primary and secondary data (deductive). The research results indicated several things. First, Consistency between the governance of higher education and legislations concerning national education system requires governance, management and administration in one national education system, namely higher education of State University (PTN), established and or administered by the Government. Concrete regulations in Article 11 (5) of Law No 2 of 1989 concerning National Education System and Article 29 and Article 15 of Law No. 20 of 2003 concerning National Education System are contradictory with the reality of the management and have impact on in-service higher education in in-service universities. The general principles of legislations, either formal or material, are not yet reflected in such regulation of higher education setting. Regulation for the administration of higher education performed by the government has not been optimal.